Collaborative communities as a selling point? From community-driven to service-purposed coworking spaces - Orel, Marko; Bennis, Will (European Spatial Research and Policy, 2021)
Coworking spaces emerged in the mid-2000s as collaborative workplaces that actively supported teleworkers and self-employed knowledge workers who shared various (work) environments to interlace themselves in supportive networks, tackle isolation, positively influence well-being, and collaboratively participate in knowledge-sharing activities. However, with the swift popularisation of the coworking model by 2020, newly established flexible office spaces have begun to refer to themselves as community-based workplaces even though they lacked the capacity to support their users’ interactions and collaborative work. Therefore, the purpose of the paper is to explore how coworking spaces have transformed from community-based environments to a flexible place of work where establishing a collaborative community is not an organisational priority. The following exploratory research investigates a sample of 13 coworking spaces in Prague, the Czech Republic, and considers their capacity for supporting interactions and collaborative processes between their users. The results uncovered significant differences between coworking spaces, their spatial designs, the presence of mediation mechanisms, and the frequency of interactions between users, and suggest that the handful of sampled coworking environments misuse the notion of community. In that context, the following study indicates that contemporary coworking spaces can revert to community washing to deliberately pursue economic self-interest rather than support decentralised peer-to-peer exchange that would lead to developing a coworking community. * The research was funded by the Czech Science Foundation (GACR), grant number 20-06716S.